Thyroid Hormone, Thyroid Hormone Metabolites and Mast Cells: A Less Explored Issue - Landucci, Elisa; Laurino, Annunziatina; Cinci, Lorenzo; Gencarelli, Manuela; Raimondi, Laura (Frontiers in Cellular Neuroscience, 2019)
Mast cells are primary players in immune and inflammatory diseases. In the brain, mast cells are located at the brain side of the blood brain barrier (BBB) exerting a crucial role in protecting the brain from xenobiotic invasion. Furthermore, recent advances in neuroscience indicate mast cells may play an important role in glial cell-neuron communication through the release of mediators, including histamine. Interestingly, brain mast cells contain 50% of the brain histamine but also hormones, proteases and lipids or amine mediators and cell degranulation may be triggered by different stimuli activating membrane bound receptors including the four types of histaminergic receptors. Among hormones, mast cells can store thyroid hormone (T3) and express membrane-bound TSH receptors, thus suggesting from one side that thyroid function may affect mast cells function, from the other that mast cell degranulation may impact on thyroid function. In this respect , the research on hormones in mast cells is scarcely. Recent pharmacological evidence indicates the existence of a non-genomic portion of the thyroid secretion including thyroid hormone metabolites. Among which the 2,3,didiodothyronine (3,5T2), 3-iodothyroanamine (T1AM) and 3-iodothryoacetic acid (TA1) are the most studied. All these compounds are endogenously occurring and found increased in inflammatory-based diseases involving mast cells. T1AM and TA1 induce, as T3, neuroprotective effects and itch but also hyperalgesia in rodents with a mechanism largely unknown but mediated by the release of histamine . Due to the rapid onset of their effectiveness they may trigger histamine release from a cell where it is “ready-to-be released”, i.e. mast cells. Following a very thin path which passes through old experimental and clinical evidence, at the light of novel acquisitions on endogenous T3 metabolites, we aim to stimulate the attention on the possibility that mast cell histamine may be the connector of a novel (neuro)endocrine pathway linking the thyroid with mast cells.